Peran Hukum Ekonomi dalam Implementasi Green Banking Sebagai Upaya Mendukung Ekonomi Hijau di Indonesia - Riyadi, Qurratu’ Ain Bintang; Ramadhan, Diva Rizky; Kusnadi, Nandang (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
Green banking plays a significant role in supporting the development of a green economy through the application of sustainable finance principles in the banking sector. In this context, economic law functions as a strategic framework to regulate and encourage the integration of environmental, social, and governance (ESG) aspects in banking activities. This study aims to examine the role of economic law in the implementation of green banking in Indonesia and to identify the legal challenges involved. This research adopts a normative legal method using statutory and conceptual approaches. The findings reveal that regulations on sustainable finance issued by the Financial Services Authority have provided a legal basis for the implementation of green banking. However, challenges remain, including regulatory disharmony, weak law enforcement, and limited institutional capacity and commitment within the banking sector. Therefore, strengthening the role of economic law through regulatory improvement and effective supervision is essential to ensure that green banking can optimally support the realization of a sustainable green economy in Indonesia.